Nematode-Trapping Fungi in Biological Control of Dictyocaulus viviparus - Henriksen, Sv. Aa. (Acta Vet Scand, 1997)
Larvae of the cattle lungworm Dictyocaulus viviparus were cultured in experimental units of 200 g cattle faeces placed in semi-transparent trays in the laboratory. In each of 4 experimental series using this experimental unit, chlamydospores (chl) of the nematode-trapping fungus Duddingtonia flagrans were admixed to half of the faecal cultures in a concentration of 50.000 chl/g. In all 4 series there was a significant reduction in the development and subsequent release of infective lungworm larvae from faecal cultures containing chlamydospores. The average reduction in larval release, caused by fungal spores, was 86%.